2021
DOI: 10.1177/13684302211038058
|View full text |Cite
|
Sign up to set email alerts
|

Can ingroup love harm the ingroup? Collective narcissism and objectification of ingroup members

Abstract: We examined how collective narcissism (a belief in ingroup greatness that is underappreciated by others) versus ingroup identification predicts treatment of ingroup members. Ingroup identification should be associated with favorable treatment of ingroup members. Collective narcissism, however, is more likely to predict using ingroup members for personal gain. In organizations, collective narcissism predicted promoting one’s own (vs. group) goals (prestudy: N = 179), and treating coworkers instrumentally (Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 87 publications
(162 reference statements)
2
46
0
Order By: Relevance
“…On the other hand, it could also be linked to, or at least not opposed to, support for conservative ideas and movements that may conflict with the interests of the ingroup (see also Jost et al, 2017). This finding supports research showing that people with high levels of collective narcissism are more concerned with their own self-interest than with the interest of the group, possibly leading to attitudes and behaviours that undermine the ingroup and its members (e.g., disloyalty, objectification of ingroup members, Cichocka et al, 2021;Gronfeldt et al, 2022;Marchlewska et al, 2020).…”
Section: Variablesupporting
confidence: 87%
See 2 more Smart Citations
“…On the other hand, it could also be linked to, or at least not opposed to, support for conservative ideas and movements that may conflict with the interests of the ingroup (see also Jost et al, 2017). This finding supports research showing that people with high levels of collective narcissism are more concerned with their own self-interest than with the interest of the group, possibly leading to attitudes and behaviours that undermine the ingroup and its members (e.g., disloyalty, objectification of ingroup members, Cichocka et al, 2021;Gronfeldt et al, 2022;Marchlewska et al, 2020).…”
Section: Variablesupporting
confidence: 87%
“…Thus, the positive association between secure identity and support for collective action on behalf of the ingroup may be particularly pronounced among members of disadvantaged groups (see Cichocka et al, 2021).…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…We seek to examine whether the way people feel about their groups might also be associated with conspiratorial intentions. We argue that those high in collective narcissism -that is, those who tend to use their group for personal gains (Cichocka et al, 2021;Marchlewska et al, 2020) -might be willing to engage in conspiracies against other group members to achieve their own selfish goals. Below, we discuss past work on collective narcissism, highlighting its implications for conspiracy beliefs, followed by our theoretical rationale for why this form of in-group identity might also predict intentions to engage in conspiracies.…”
Section: Practitioner Pointsmentioning
confidence: 97%
“…During the COVID‐19 pandemic, those high in national narcissism reported engaging in hoarding resources (Nowak et al., 2020). Evidence from the organizational context has also shown that collective narcissists try to benefit personally by treating their co‐workers in an instrumental way (Cichocka, Cislak, Cislak, Gronfeldt, & Wojcik, 2021). Crucially, those scoring high in collective narcissism were also ready to engage in non‐democratic practices and conspire against fellow group members.…”
Section: Concept Definitionmentioning
confidence: 99%